Individual differences in basic cognitive processes and self-regulated learning: their interaction effects on math performance - Musso, Mariel Fernanda (2019)
The study analyzes the relationships between working memory capacity, executive attention, and self-regulated learning (SRL) on math performance (MP), and more specifically on items with different levels of complexity and difficulty. Sample: 575 university students (female: 47.5%; 18?25 years old), first academic year. Instruments: Attention Network Test; Automated Operation Span; Mathematics Test; On-line Motivation Questionnaire, and Learning Strategies Questionnaire. Results confirm the crucial role of individual differences in WMC that impact directly on MP, mediated by subjective competence. Affective SRL contribute significantly as mediating variables but their positive effect depends on the availability of cognitive resources. Findings partially confirmed the differential contribution of cognitive processes in the prediction of performance in complex vs difficult items. We found support for a complex pattern of interactions between cognitive processes and components of SRL model at the strategy level, in their effect on MP, and given specific item characteristics.